PENGGUNAAN METODE PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KEMAMPUAN MENGARANG PUPUH GINADA OLEH SISWA KELAS X TATA BOGA SMK PGRI 4 DENPASAR TAHUN PELAJARAN 2020/2021 - Luh De Liska (Universitas Mahendradatta Denpasar, 2022)
The material for composing pupuh has been taught in schools according to the curriculum used at SMK PGRI 4 Denpasar, but student achievement in composing Pupuh Ginada is still felt below. This can be proven from the pre-test conducted before this research was carried out. The test shows that there are still many students who have difficulty composing Ginada's pupuh. In addition, the average score of Ginada's pupuh composing ability in the pre-test results was below the minimum completeness criteria (KKM) set at school, namely 76. The purpose of this study was to improve the ability to compose Ginada's pupuh and student responses during the learning process. The subjects of this study were all students of Class X Catering at SMK PGRI 4 Denpasar, totaling 46 people. The data collection methods used were the test method, the observation method, and the questionnaire method. The average value of Ginada's pupuh writing ability using the jigsaw type cooperative learning method Class X Catering at SMK PGRI 4 Denpasar for the 2020/2021 academic year reached 82% with a very good category. Based on the results of questionnaires and observations showed a significant increase in the average value, namely the questionnaire of 87% and the observation of 94%. Based on the average value, it can be concluded that the use of the jigsaw type of cooperative learning method can improve the ability to compose Ginada's pupuh in Class X Catering SMK PGRI 4 Denpasar in the 2020/2021 school year, and the use of cooperative learning methods to compose Ginada's pupuh received a very positive response. positive from students.